Online Shopping Behavior of Employees of PT Bukit Asam Tbk Tanjung Enim Mining Unit - Cristian, Andi; Gunarto, Muji; Helmi, Sulaiman (International Journal of Marketing & Human Resource Research, 2025)
This study investigates the online shopping behavior of employees at PT Bukit Asam Tbk (PTBA) Tanjung Enim Mining Unit. Using a qualitative case study method, data were collected through in-depth interviews with ten purposively selected respondents. The findings highlight convenience, promotions, and social influences as key factors shaping online shopping habits, alongside challenges such as financial control and shopping addiction. The study provides insights into consumer behavior dynamics among mining employees and offers recommendations for improving financial management and online shopping platforms.